Dialogisation and interdisciplinary integration of the content of the learning process as a schoolchild’s giftedness factors - Irina S. Dyshlyuk; Irina Yu. Kameneva; Anna Е. Moskalenko (Rossijskij psihologičeskij žurnal., 2017)
Giftedness is an integral feature of personality. The paper deals with the problem of the development of giftedness in mass education without isolating a gifted child from the natural microenvironment. Pedagogical activities should be carried out in the context of schoolchildren’s personal development. To develop schoolchildren’s giftedness, the learning content should be active, conceptual, problem, and personal-sense, as well as include schoolchildren’s personal experience. Dialogisation and interdisciplinary integration are ways for constructing a content of that type. Dialogisation of the learning content brings it to a personal-sense level, increases its problem and conceptual characteristics. In personality-oriented education schoolchildren solve learning tasks as vital. These tasks (a) do not have one correct solution, (b) attract schoolchildren’s interest, and (c) increase their academic motivation. The components entering into a dialogue construct the dialogue content. Hence, activity is inherent in it. The components representing the content of various subjects or subject areas can be a powerful educational force. The integrated content intensifies the subject content, imparts personal sense to certain disciplines, enables gifted children to use and develop their flexibility, metaphoricalness, and associative thinking. The integrated content promotes the development of system and conceptual thinking. A sufficient level of conceptual thinking is necessary for forming interdisciplinary concepts. Dialogisation and integration of the learning content are especially important for the acquisition of interdisciplinary intellectual tools and the development of metasubject abilities. These processes are urgent objectives in modern Russian schools.